In Haitian women and preschool children, iron absorption from wheat flour-based meals fortified with sodium iron EDTA is higher than that from meals fortified with ferrous fumarate, and is not affected by Helicobacter pylori infection in children. Issue 4 (6th September 2017) - Herter-Aeberli, Isabelle; Eliancy, Kerline; Rathon, Yanick; Loechl, Cornelia U.; Marhône Pierre, Joseline; Zimmermann, Michael B.
Abstract: Fe fortification of wheat flour was proposed in Haiti to combat Fe deficiency, but Fe bioavailability from fortificants has never been investigated in Haitian women or preschool children, two key target groups. We aimed to investigate the bioavailability of ferrous fumarate (FeFum), NaFeEDTA and their combination from fortified wheat flour. We recruited twenty-two healthy mother–child pairs in Port au Prince, Haiti, for an Fe-absorption study. We administered stable Fe isotopes as FeFum or NaFeEDTA individually in low-extraction wheat flour bread rolls consumed by all participants in a randomised, cross-over design. In a final, identical meal, consumed only by the women, FeFum+NaFeEDTA was administered. We measured Fe absorption by using erythrocyte incorporation of stable isotopes 14 d after consumption of each meal, and determined Fe status, inflammatory markers and Helicobacter pylori infection. Fe absorption (geometric mean was 9·24 (95 % CI 6·35, 13·44) and 9·26 (95 % CI 7·00, 12·31) from FeFum and 13·06 (95 % CI 9·23, 19·10) and 12·99 (95 % CI 9·18, 18·39) from NaFeEDTA in mothers and children, respectively ( P <0·05 between compounds). Fe absorption from FeFum+NaFeEDTA was 11·09 (95 % CI 7·45, 17·34) and did not differ from the other two meals. H. pylori infection did not influence Fe absorption in children. In conclusion, in Haitian women and children, Fe absorption from NaFeEDTA was 40 % higher than from FeFum, and the combination FeFum+NaFeEDTA did not significantly increase Fe absorption compared with FeFum alone. In the context of Haiti, where the high costs of NaFeEDTA may not be affordable, the use of FeFum at 60 mg Fe/kg flour may be a preferable, cost-effective fortification strategy.